2018
DOI: 10.1007/978-3-319-76270-8_55
|View full text |Cite
|
Sign up to set email alerts
|

Using a Serious Game to Assess Spatial Memory in Children and Adults

Abstract: Short-term spatial memory has traditionally been assessed using visual stimuli, but not auditory stimuli. In this paper, we design and test a serious game with auditory stimuli for assessing short-term spatial memory. The interaction is achieved by gestures (by raising your arms). The auditory stimuli are emitted by smart devices placed at different locations. A total of 70 participants (32 children and 38 adults) took part in the study. The outcomes obtained with our game were compared with traditional method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…Motor inhibition, mental flexibility and control of impulse responses were exhibited. Auditory spatial memory test Karotz Rabbits test [ 70 ] 9.5 32 TD ___ ___ Children at these ages did not demonstrate this competence. [ 71 ] 1.3 46 TD ___ Rotational angles 18-month-olds used a self-reference system, modulating searches in conjunction with directions and distances.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Motor inhibition, mental flexibility and control of impulse responses were exhibited. Auditory spatial memory test Karotz Rabbits test [ 70 ] 9.5 32 TD ___ ___ Children at these ages did not demonstrate this competence. [ 71 ] 1.3 46 TD ___ Rotational angles 18-month-olds used a self-reference system, modulating searches in conjunction with directions and distances.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies focused on children from four years of age, four of them on children from six to twelve years old [ 10 , 66 , 63 , 70 ] and most of the studies included in this review considered participants from preschool to twelve years old. From five years onwards, spatial memory starts to improve.…”
Section: Resultsmentioning
confidence: 99%
“…For external assessment, the students were provided with MCQ or interviews after the GBA. Three studies compared the effectiveness of GBA and traditional tests, Hsu et al (2011), Loachamín-Valencia et al (2018 and Neumann and Neumann (2019). These studies concluded that GBA is better than pen and paper formats.…”
Section: Task Performance In Gba Studiesmentioning
confidence: 99%